2019
DOI: 10.1080/23802359.2019.1660250
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the complete mitochondrial genome sequence ofAsiadodis yunnanensis (Mantidae: Choeradodinae) and phylogenetic analysis

Abstract: The complete mitochondrial genome of the praying mantises Asiadodis yunnanensis was characterized in this study. The circular molecule is 15,416 bp in length (GenBank accession no. MN037794), containing 13 protein-coding genes (PCGs), two ribosomal RNA (rRNA) genes, 22 transfer RNA (tRNA) genes. The nucleotide composition is asymmetric (39.5% A, 15.1% C, 9.6% G, 35.8% T), with an overall A þ T content of 75.3%. The gene arrangement of A. yunnanensis is identical to that observed in other praying mantises. Seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 3 publications
1
2
0
Order By: Relevance
“…The phylogenetic tree was constructed using the maximum-likelihood method through IQtree 1.6.8 (Nguyen et al 2015). Results showed that the family Mantidae is not monophyletic and P. breve clustered into a clade with congeneric species (Figure 1), which was consistent with the previous studies (Legendre et al 2015;Le-Ping et al 2018;Shi et al 2019). As a conclusion, we obtained and described the complete mitochondrial genome of P. breve, which constitute a valuable and useful resource for population genetic study and identification efforts on this species.…”
supporting
confidence: 85%
“…The phylogenetic tree was constructed using the maximum-likelihood method through IQtree 1.6.8 (Nguyen et al 2015). Results showed that the family Mantidae is not monophyletic and P. breve clustered into a clade with congeneric species (Figure 1), which was consistent with the previous studies (Legendre et al 2015;Le-Ping et al 2018;Shi et al 2019). As a conclusion, we obtained and described the complete mitochondrial genome of P. breve, which constitute a valuable and useful resource for population genetic study and identification efforts on this species.…”
supporting
confidence: 85%
“…not being a Hierodulinae. The systematic status of Mesopteryx and phylogenetic relationships among subgroups within the Hierodulinae are still unresolved (Guan et al, 2020;Shi et al, 2019;Xu et al, 2021;Zhang et al, 2018aZhang et al, , 2018bZhang et al, , 2019 and it needs to be re-evaluated by a combination of morphological characteristics and molecular data.…”
Section: Phylogenetic Analysismentioning
confidence: 99%
“…As of 28 June 2022, about 27 complete or nearly complete mitogenomes of Hierodulinae species have been sequenced since the first mitogenome of Mantodea, Tamolanica tamolana Brancsik, 1897 was obtained [ 15 ]. Mitochondrial phylogenomic studies of Mantodea in the past five years [ 16 , 17 , 18 , 19 , 20 ] have shown generally congruent relationships compared to the current classification in derived Heteromantodea.…”
Section: Introductionmentioning
confidence: 89%